INCREASED TIBIOFEMORAL ROTATION WITH INCREASING SEVERITY OF PATELLAR INSTABILITY. Issue 4 (28th April 2020) - Lin, Kenneth M.; James, Evan W.; Schlichte, Lindsay; Wang, Grace; Green, Daniel
Background: Tibiofemoral rotation (TFR), specifically external tibial rotation, has been recently identified as a potential contributing factor to patellar instability. However, no previous studies have explored the clinical effects of differing degrees of TFR in relation to patellar instability. Purpose and Hypothesis: The purpose of this study is to investigate the relationship between severity of instability with degree of TFR. Our hypothesis is that fixed or obligatory dislocators (FOD) are more likely to have increased external TFR (tibial external rotation compared to femur) than standard patellar instability (SPI) patients requiring medial patellofemoral ligament (MPFL) reconstruction, who will have similar or slightly increased external TFR compared to normal controls. Methods: A retrospective study was performed with patients from 3 cohorts from April 2009 to February 2019: FOD, SPI, and controls with normal magnetic resonance imaging (MRI) of the knee. All FOD patients from the study time frame were analyzed, while controls and SPI patients were randomly selected. Patients were included for age under 18 years and diagnosis corresponding to one of the three cohorts, and excluded for outside institution MRI, and previous MPFL reconstruction or tibial tubercle osteotomy. TFR was measured on preoperative axial MRI using the posterior femoral and tibial condylar lines (Figure 1). Tibial tubercle to trochlear groove distance (TT-TG) was measured. Intraclass correlation coefficient (ICC) was calculated among 3 measurers. Statistical analysis using ANOVA and t-test was performed with significance set at α=0.05. Results: A total of 57 patients were included, 19 in each cohort. Average age was 13.2 years (range 10-17 years), with 31 females (54%). ICC for TT-TG and TFR were 0.90 and 0.72, respectively. TT-TG differed between the controls and SPI patients (both P<0.001), and controls and FOD patients (P<0.001), but not between SPI and FOD patients (P=0.12). TFR differed among the three groups: 8.4° (SD 16.7°) external TFR in FOD, 1.6° (SD 5.4°) external TFR in SPI, and 2.5° (SD 5.8°) internal TFR in controls (P=0.0089). FOD patients had significantly greater external tibial rotation than the SPI group (P=0.047). Conclusions: The degree of TFR is correlated with severity of patellar instability, with greater external tibial rotation seen in FOD than SPI patients, while TT-TG was not different. Further information on the relationship of TFR and patellar instability will not only improve understanding of pathogenesis and prognosis, but may also direct surgical treatment strategies in refractory or severe cases. : Figure 1. Measurement of tibiofemoral rotation (TFR) using proton density axial MRI. A: The posterior femoral condylar line at the level of the anterior-posterior diameter of the condyles is drawn.B: The angle of the posterior femoral condylar line is drawn against the posterior tibial line, at the level of the PCL insertion onto bone. Figure 2. Comparison of MRI TFR and TT-TG by severity of patellar instabillity. A: TFR increases significatly with increased severity of patellar instabillity, and is significantly greater in FOD patients than SPI patients. B: TT-TG is significantly increased in patellar instabillity patients compared to controls, but is ot significantly different between SPI and FOD patients.